Building DIY (Do-It-Yourself) Based Resilience: A Denpasar Kolektif Experience in the Pandemic Crisis - Wirawan, I Gusti Made Arya Suta; Kangto, Sanggar; Aminuddin, M. Faishal; Putri, L.G Saraswati (Journal of Ecohumanism, 2024)
This study shows that the Covid-19 pandemic has not reduced the existence of collectivism and activism of a punk community in Denpasar City called Denpasar Kolektif (Denkol). The pandemic has not only led Denkol to build resilience for itself. With all the capital available, they are more active in building resilience for other social groups, especially those marginalized during the pandemic. Denkol does not only accommodate the catharsis of young people in expressing themselves during and after the pandemic. They also maximize the function of public spaces that the punk community has not filled during the pandemic. By prioritizing a qualitative phenomenological approach, the study shows that Denkol has built an inclusive habitus while running creative events during the pandemic. This inclusivity is essential not only for opening up critical space for the Balinese people towards various issues such as environmental issues, marginalization, mental health, and other things affected by the pandemic but also for self-criticism within the punk body itself, which is considered hegemonic. The increasingly inclusive fields also gave rise to decentralized activism, emphasizing that punk as a subculture opened space for creating plurality, fragmentation, and relativity within it.